Perceptions of patient safety culture among medical students: a cross-sectional investigation in Heilongjiang Province, China. Issue 7 (12th July 2018) - Liu, He; Li, Ying; Zhao, Siqi; Jiao, Mingli; Lu, Yan; Liu, Jinghua; Jiang, Kexin; Fang, Huiying; Sun, Peihang; Li, Peng; Wang, Yameng; Jia, Haonan; et al.
Abstract : Objectives: Medical school education plays an important role in promoting patient safety. In this study, we assess medical students' perceptions of patient safety culture, identify their educational needs and provide evidence on the most important content relating to patient safety for the medical school curriculum. Method: This cross-sectional study was conducted in four medical universities in Heilongjiang province. Medical students in the first through five years completed an anonymous questionnaire—the Attitudes toward Patient Safety Questionnaire III. We analysed the differences in responses across the four universities and their cohorts. Results: The overall perceptions of patient safety culture across the four medical universities were positive. The highest positive response rate was for 'I have a good understanding of patient safety issues as a result of my undergraduate medical training' (range: 58.4%–99.8%), whereas the lowest positive response rate was for 'medical errors are a sign of incompetence' (14.7%–47.9%). Respondents in the earlier years of school tended to have more positive responses for items concerning working hours and team work; however, fourth and fifth year students had more positive responses for error inevitability. Items with the lowest positive response rates across the cohorts included items related to 'professional incompetence as a cause of error' and 'disclosure responsibility'. Conclusions: While students generally had positive views of patient safety culture, none of them had been exposed to any formal curriculum content on patient safety. Policymakers should focus more on how educational needs vary across schools and cohorts in order to establish appropriate curricula.